The Effect of Jigsaw Learning Method on Improving Students' Religious Education Learning Outcomes: A Meta-Analysis - Dirman; Boy, La; Erdiyanti; Raehang (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study investigates the effectiveness of the Jigsaw-type cooperative learning model in improving Islamic Religious Education (PAI) learning outcomes through a meta-analysis of 13 quantitative studies published between 2011 and 2025. The studies employed various experimental designs, and the analysis used effect size measurements based on Cohen’s d and N-Gain. Results indicate significant improvements in learning outcomes and student motivation, with effect sizes ranging from 0.51 to 1.132—interpreted as moderate to very strong effects. The highest impact was recorded by Aziz et al.’s (2024), while Rahmiati et al.’s (2022) showed moderate gains. Correlational studies and surveys also reported consistent positive effects on students’ cognitive and affective aspects. These findings reinforce the relevance of the Jigsaw model as an effective pedagogical strategy in PAI instruction across education levels. The study recommends broader adoption of this model in the PAI curriculum and emphasizes the need for enhanced teacher training to ensure successful implementation.